Periodic solutions for indefinite singular equations with singularities in the spatial variable and non-monotone nonlinearity - Amster, Pablo Gustavo (2018)
TWe prove the existence of T−periodic solutions for the second order non-linear equation u0 1 − u02 0 = h(t)g(u), where the non-linear term g has two singularities and the weight function h changes sign. We find a relation between the degeneracy of the zeroes of the weight function and the order of one of the singularities of the non-linear term. The proof is based on the classical Leray-Schauder continuation theorem. Some applications to important mathematical models are presented.